Historical-Critical Dictionary of Marxism a selection - Baehrens, Konstantin 1984-; Koivisto, Juha; Strazzeri, Victor (Historical materialism book series, 2023)
The Historical-Critical Dictionary of Marxism (HCDM) is a comprehensive Marxist lexicon, which in the 9 German-language volumes concluded so far has involved over 800 scholars from around the globe. Conceived by philosopher Wolfgang Fritz Haug in 1983, the first volume of the ongoing lexicon project was published in 1994. This first English-language selection introduces readers to the HCDM’s wide range of terms: besides Marxist concepts, approached from a plural standpoint and stressing feminist, ecological, and internationalist perspectives, it boasts entries on the histories of social movements, theoretical schools, as well as cultural, political, philosophical, and aesthetic debates.